Rechargeable lithium battery employing a new ambient temperature hybrid polymer electrolyte based on PVK+PVdF–HFP (copolymer) - Michael, M.S.; Prabaharan, S.R.S. (2004)
We describe here for the first time, our recent success in developing an ambient temperature Li+ conducting solid polymer electrolyte (SPE) using the concept of polymer alloying upon blending two thermoplastic polymers such as poly(vinylidene) fluoride-hexafluoropropylene (PVdF-HFP-copolymer) and poly(N-vinylcarbazole), PVK and achieved the room temperature electrolytic conductivity (sigma(i)) of 0.7 x 10(-3) S/cm for a typical composition of PVdF-HFP copolymer/PVK blend mixed with EC/LiBF4 molar composition. The ionic transference number of 0.49 was deduced from combined ac-impedance and do polarization method. High-resolution optical microscopic examination revealed the disappearance of characteristic highly porous surface structure of PVdF-HFP matrix upon blending with PVK leading to the formation of resultant PVdF-HFP/PVK blend polymer alloy. The electrochemical stability of the polymer electrolyte membrane thus obtained was found to be stable up to similar to4.7 V versus Li/Li+. The new hybrid alloy polymer electrolyte membrane was found to exhibit good interfacial properties against lithium metal and thus, it was found to aid the room temperature operation as electrolytic membrane cum separator in all-solid state rechargeable lithium polymer test cell, LiCo0.8Ni0.2O2/SPE/Li. (C) 2004 Elsevier B.V. All rights reserved.